(untitled) (Journal of Engineering, 2010)
This paper presents region growing image segmentation method which unifies region and boundary information. Several studies shown that segmentation based on image features can improve the accuracy of the interpretation. The goal of segmentation is to simplify and/or change the representation of an image into something that is more meaningful and easier to analyze. Image segmentation is typically used to locate objects and boundaries (lines, curves, etc.) in images. More precisely, image segmentation is the process of assigning a label to every pixel in an image such that pixels with the same label share certain visual characteristics. A problem that frequently arises when an image is segmented is that the number of feature variables or dimensionality is often quite large. It becomes necessary to decrease the number of the variables to manageable size. The other main difficulty of traditional image segmentation is the lack of adequate tools to characterize different scales of image effective. In this paper it proposed three dimension multiwavelet algorithm to overcome this difficulty and then the region growing method is applied to segment this image.